Antifungal activity of Terminalia chebula fruit extracts - Venkatachalam, P.; Chittibabu, C.V. (Current Botany, 2020)
The present study was aimed to investigate the anticandidal and antifungal potential of dried fruit extracts of Terminalia chebula against Candida albicans, C. tropicalis C. glabrata, C. krusei, C. parapsilosis, and Aspergillus flavus, A. niger, A. fumigatus, Trichophyton mentagrophytes, T. rubrum, Microsporum gypseum. Phytochemical analysis of methanol extracts of T. chebula dried fruits showed the presence of flavonoids, alkaloids, glycosides, saponins, tannins, terpenoids and steroids. Among the tested four extracts, the methanol extracts of T. chebula dried fruits exhibited the highest antifungal activity and their inhibition zone was ranged between 7.5 to 19.5mm. MIC and MFC values were between 62.5-250μg/ml and 250-500μg/ml respectively. Zone of inhibition (19.5 mm), MIC (62.5µg/ml) and MFC (125µg/ml) values observed in methanolic extracts of T. chebula dried fruits against A. fumigates and T. mentagrophytes. Our findings proved that methanolic extracts of T. chebula dried fruits were possessed substantial anticandidal and antifungal properties.